GROUNDWATER CHARACTERISTICS IN JAKARTA AREA, INDONESIA - Makoto Kagabu; Robert M. Delinom; Rachmat Fajar Lubis; Jun Shimada; Makoto Taniguchi (Indonesian Institute of Sciences, 2010)
ABSTRACT In the Jakarta area (Indonesia), excessive groundwater pumping due to the rapidly increasing population has caused groundwater-related problems such as brackish water contamination in coastal areas and land subsidence. In this study, we adopted multiple hydrogeochemical techniques to understand groundwater characteristic in the Jakarta area. Although almost all groundwater existing in the Jakarta basin is recharged at similar elevations, the water quality and apparent residence time demonstrates a clear difference between the shallow and deep aquifers. Due to the rapid decrease in the groundwater potential in urban areas, we found that the seawater intrusion in shallow aquifer and the shallow and deep groundwaters are mixing, a conclusion confirmed by major ions, Br−:Cl− ratios and chlorofluorocarbon (CFC)-12 analysis.